Solution chemistry of sulphide mineral flotation in recycled water and sea water: a review. (3rd July 2017) - Rao, F.; Lázaro, I.; Ibarra, L. A.
Abstract : The use of low-quality water in sulphide minerals flotation plants has been studied widely. However, implementation of the strategy of low fresh water consumption and low process-affected water disposal in sulphide flotation requires a comprehensive understanding of the impacts of solution chemistry on sulphide minerals flotation. Such impacts as buffering effect, slime coating, inadvertent activation and depression, and changes in pulp potential and frothability on sulphide minerals flotation are reviewed and discussed in this paper. Typical practises of Cu–Pb–Zn sulphide flotation with recycled water, and copper sulphide flotation with sea water in Atacama Desert in Chile are presented.